Costs of colorectal cancer screening in Sweden: an observational, longitudinal cost description - Johannes Blom; Naimi Johansson; Camilla Nystrand (BMJ Open Gastroenterology)
Objective Colorectal cancer (CRC) screening programmes have been implemented worldwide, but the evidence of the economic consequences of screening programmes relies on data from short-term trials. The aim of this paper was to describe the costs of CRC screening in a population-based screening programme, using administrative real-world data. Specifically, we aimed to estimate the annual costs of the screening programme and the total costs of the full programme over five consecutive screening rounds.Methods The CRC screening programme of Stockholm-Gotland, Sweden, targeted all resident men and women aged 60–69 years for biennial screening. The screening strategy was faecal occult blood testing (FOBT) sent to individuals’ home addresses, with a positive test result leading to an invitation to diagnostic colonoscopy. The cost description was conducted with a retrospective, bottom-up costing design from a healthcare perspective using (1) a prevalence-based approach and (2) an incidence-based approach, with two different study samples.Results Annual healthcare costs were estimated using a sample of 124 608 individuals who were affected by the screening programme in 2017. Annual healthcare costs of the screening programme summed up to €273 758 per 10 000 people, equivalent to €27.4 per eligible individual. The sum of costs for colonoscopy procedures was more than two times as high as the costs for FOBT. The costs of the full screening programme were estimated using a cohort of 92 689 individuals who were invited to five consecutive rounds of screening between 2009 and 2021. Total healthcare costs over five screening rounds were €960 654 per 10 000 people, equivalent to €96.1 per individual.Conclusion The costs of diagnostic colonoscopies for a minority of participants were driving the costs of the CRC screening programme. The ongoing population-based screening programme and high-quality individual level data with long-term follow-up provide the opportunity to thoroughly describe the costs of CRC screening.